The attenuating effect of green finance on environmental quality and its mechanism: spatial modified PTRM model - Tang, Xinmeng; Qin, Tao; Nazief Haggag Kotb Kholaif, Moustafa Mohamed; Zhao, Xinyan (Elsevier Ltd, 2024)
The traditional Panel Threshold Regression Model (PTRM) neglects spatial factors, causing model bias in prior research on green finance's environmental impact. To address this shortcoming, a Spatial Modified PTRM Model is constructed to investigate green finance's spatial threshold effects on the environment. Moreover, this study analyzes temporal and regional heterogeneities and explores the influence mechanisms underlying the observed attenuating in environmental effects. Results show that: (1) The “more developed, less effective” phenomenon in green finance's environmental impact is confirmed, instead of cumulative enhancement, as green finance intensity surpasses thresholds around −0.48 to −0.61, its effects decrease by approximately 66.3–156.1 units. (2) Temporal and regional heterogeneities in the attenuating phenomenon are explored, in 2015, the attenuation phenomenon initiates, transitioning from statistical ''insignificance'' to ''significance'', from ''rapid development'' to ''plateau'', and from ''single high-value peak'' to ''single low-value peak'', also, developed green finance regions experience the most significant attenuation, up to 76.0 more pronounced than less developed regions. (3) The unbalanced regional distribution and the free-riding phenomenon are confirmed as two factors contributing to the attenuation, with the ellipse center shifting southward and the index deviating since around 2015, meanwhile, the free-riding intensity has increased over time, surging from around 0.10 in the early stages to approximately 0.40 in 2021.